Investigation of film thickness uniformity in inkjet printing of liquid optically clear adhesive - Yahao Ren; Wei Song; Yang Zhang; Lixin Wang; Zhuli Liu; Shaoqi Wang; Zunlong Jin; Changliang Wang (AIP Advances)
The inkjet printing process of liquid optically clear adhesive film often leads to the phenomenon of end protrusions, which cause bubbles during subsequent bonding and encapsulation processes or localized Mura defects. To gain a deeper understanding of the mechanism behind the formation of protrusions during film retracts, we derived a dynamic model for the formation of end protrusions in the film. This research also simulated the coalescence of multiple droplets into a film line, including protrusion formation, using the volume of fluid method. The simulation results were compared with theoretical calculations, revealing that the theoretical values were approximately twice as large as the simulated ones. We discovered that the formation of protrusions is the result of the interaction between surface tension and internal forces within the liquid film. During this process, the maximum height of the film line exhibits a positive correlation with the power of time. Finally, the influence of contact angle on the uniformity of film thickness was also explored. It was found that a smaller contact angle can suppress the occurrence of protrusions, leading to a significant improvement in the uniformity of film thickness.